2022
DOI: 10.1371/journal.pone.0276625
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, identification and antibiotic resistance profile of thermophilic Campylobacter species from Bovine, Knives and personnel at Jimma Town Abattoir, Ethiopia

Abstract: Thermophilic Campylobacter species are common cause of animal and human bacterial diseases with growing resistance to antimicrobials. The aim of this study was to determine the prevalence and antimicrobial susceptibility pattern of Campylobacter species from bovine, knives and personnel in Jimma Town, Ethiopia. Faecal samples and carcasses swabs were collected from cattle systematically selected from the annual plan of Jimma Municipal Abattoir. Personnel hand and knife swabs were collected after slaughtering e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 36 publications
4
10
1
Order By: Relevance
“…A convenient sampling technique was employed for the patient that fulfilled the inclusion criteria during the study period. Based on a previous prevalence rate of 16.7% from Jimma, Ethiopia, 30 a 95% confidence interval, and a 5% margin of error, the sample size was determined using a single population proportion formula:…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A convenient sampling technique was employed for the patient that fulfilled the inclusion criteria during the study period. Based on a previous prevalence rate of 16.7% from Jimma, Ethiopia, 30 a 95% confidence interval, and a 5% margin of error, the sample size was determined using a single population proportion formula:…”
Section: Methodsmentioning
confidence: 99%
“…The specimen was transported with Cary Blair transport medium to Mekelle University, Ayder Comprehensive Specialized Hospital, Medical Microbiology laboratory in an ice-cold box within 4 h of collection and processed immediately. 30
Figure 1 Schematic illustration of the experimental work flow.
…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Te well-being notion totally fts in the quality of life (QoL) broad-ranging concept, whose key objective in older population is to permit an active and healthy ageing, to maintain autonomy and independence, promoting physical and mental health, social inclusion, in need-of-care people, too. For these reasons, the main objective of caring for older people should be proposing comprehensive care, considering the environment in which older people fnd themselves, allowing a meaningful life in the period of older ages [6]. Previous works have demonstrated that for institutionalized individuals, maintaining autonomy and a good physical, mental, and social health is crucial and that this goal can be achieved through a multidisciplinary approach, which includes multicomponent physical activity (PA) programs, too [7].…”
Section: Introductionmentioning
confidence: 99%